2020
DOI: 10.3390/molecules25092258
|View full text |Cite
|
Sign up to set email alerts
|

Search for ABCB1 Modulators Among 2-Amine-5-Arylideneimidazolones as a New Perspective to Overcome Cancer Multidrug Resistance

Abstract: Multidrug resistance (MDR) is a severe problem in the treatment of cancer with overexpression of glycoprotein P (Pgp, ABCB1) as a reason for chemotherapy failure. A series of 14 novel 5-arylideneimidazolone derivatives containing the morpholine moiety, with respect to two different topologies (groups A and B), were designed and obtained in a three- or four-step synthesis, involving the Dimroth rearrangement. The new compounds were tested for their inhibition of the ABCB1 efflux pump in both sensitive (parental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 54 publications
5
19
0
Order By: Relevance
“…The specific activity in the ethidium bromide assay was found for the amine-free hydantoins with benzyloxybenzylidene moiety at position 5 (3, Figure 2) [23]. In particular, imidazolones with an amine group at position 2 or 2 and 3, demonstrated the potential ABCB1 modulating activity (4 and 5, Figure 2) stronger than verapamil [24]. Previous studies have provided useful conclusions coming from performed SAR analysis.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
See 2 more Smart Citations
“…The specific activity in the ethidium bromide assay was found for the amine-free hydantoins with benzyloxybenzylidene moiety at position 5 (3, Figure 2) [23]. In particular, imidazolones with an amine group at position 2 or 2 and 3, demonstrated the potential ABCB1 modulating activity (4 and 5, Figure 2) stronger than verapamil [24]. Previous studies have provided useful conclusions coming from performed SAR analysis.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Taking into account both, the need to find effective and pharmacologically safe ABCB1 modulators that finally would get pharmaceutical market and the growing interest of modern medicinal chemistry in multi-target drugs, it is especially promising to search for new anticancer agents, selective towards MDR cancer cells, with simultaneous MDR-reversal properties. Our previous studies indicated that some of imidazolone and hydantoin derivatives were able to modulate the efflux pump ABCB1 [22][23][24]. The specific activity in the ethidium bromide assay was found for the amine-free hydantoins with benzyloxybenzylidene moiety at position 5 (3, Figure 2) [23].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The routes for the synthesis of imidazolone ( 7 – 21 ) and thiazolone ( 22 , 23 ) derivatives are depicted in Scheme 1 , while the synthesis of compounds 7 – 10 , 12 – 17, 19 – 21, 24 – 30, 32 – 38 has been described elsewhere [ 27 , 28 ]. In the first step, Knoevenagel condensation was performed, in which imidazolidinone or thiazolidinone reacted with an appropriate aromatic aldehyde to access the intermediates, namely 5-arylideneimidazolidinones ( 24 – 30 , Scheme 1 ) or 5-arylidenethiazolidinone ( 31 , Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The UPLC/MS purity of compounds 7 – 23 was determined (%). The synthesis of intermediates 24 – 30, 32 – 38 and products 7 – 10, 12 – 17, 19 – 21 was described earlier [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%